2014
DOI: 10.1002/2014ja019960
|View full text |Cite
|
Sign up to set email alerts
|

On the performance of the IRI‐2012 and NeQuick2 models during the increasing phase of the unusual 24th solar cycle in the Brazilian equatorial and low‐latitude sectors

Abstract: It is known that the equatorial and low-latitude ionosphere is characterized with typical dynamical phenomena namely, the equatorial ionization anomaly (EIA). Accurate modeling of the characteristic variations of the EIA is more important to arrive at the correct estimation of range delays required for the communication and navigation applications. The total electron content (TEC) data from a chain of Global Positioning System (GPS) receivers at seven identified locations from equator to the anomaly crest and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(15 citation statements)
references
References 65 publications
2
13
0
Order By: Relevance
“…The main driver of fountain effect is the E x B drifts over the equator controlled by the strength of the EEJ, leading to the electron density variability in the equatorial and low latitudes. These results agree with the results shown by Venkatesh et al [2014aVenkatesh et al [ , 2014b and Kumar et al [2015a]. During the winter season, it is observed from the GPS-TEC that the EIA is weak keeping most of the ionization over the equator.…”
Section: Variations Of Dtec (Difference Between Tec From Gps and Iri-supporting
confidence: 92%
“…The main driver of fountain effect is the E x B drifts over the equator controlled by the strength of the EEJ, leading to the electron density variability in the equatorial and low latitudes. These results agree with the results shown by Venkatesh et al [2014aVenkatesh et al [ , 2014b and Kumar et al [2015a]. During the winter season, it is observed from the GPS-TEC that the EIA is weak keeping most of the ionization over the equator.…”
Section: Variations Of Dtec (Difference Between Tec From Gps and Iri-supporting
confidence: 92%
“…His results showed that the diurnal VTEC prediction performance of the model is generally better during the solar minimum phase 2009 than during solar maximum phase 2012 which is in agreement to our results in this study. Our results are also found in agreement with those reported using IRI‐NeQ topside over other low‐latitude regions [ Venkatesh et al ., ; Kumar et al ., , ].…”
Section: Resultsmentioning
confidence: 99%
“…The comparison of the IRI‐2007 model with those from NeQuick2 over East African equatorial region, also showed the similar results that the IRI‐2007 model generally overestimates the observed VTEC during the solar minimum year [ Nigussie et al ., ]. A comparative study on the morphological variations of the GPS‐TEC and its comparison with The IRI‐2012 modeled TEC over Brazillian region during ascending phase of solar activity from 2010–2013 was studied by Venkatesh et al [] which revealed that the performances of the model are improved during low solar activity periods compared to that during the high solar activity years. In contrast to this, recently, Tariku [] has shown the GPS‐VTEC variation and examine the capacity of the latest version (IRI‐2012) model with IRI‐NeQ topside in predicting the VTEC over the low‐latitude regions of Uganda during both the low and the high solar activity phases and reported the largest overestimation by the IRI‐2012 model during the low solar activity phase 2009.…”
Section: Introductionmentioning
confidence: 99%
“…The day‐to‐day variability in the diurnal variation of TEC is observed at all the locations during the three seasons, and this variability is higher around the anomaly crest locations during equinoctial months. The seasonal and day‐to‐day variabilities in TEC variations over the equatorial and low‐latitude sectors have been reported in the earlier studies using measurements from different parts of the globe [ Abdu et al , ; Mannucci et al , ; Brunini et al , ; Jee et al , , Bagiya et al ., 2009; Venkatesh et al , ; Shimeis et al , , , and references therein].…”
Section: Resultsmentioning
confidence: 99%